2017
DOI: 10.1021/acssynbio.6b00255
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Iron Responses in Mammalian Cells by Signal-Induced Protein Proximity

Abstract: A new synthetic biology engineering strategy integrating chemical reactivity sensing and small molecule induced protein dimerization has been developed to generate artificial Fe signaling circuitry to control tailored cellular events in mammalian cells. The dual function probe ABA-FE18 (Fe-sensing and protein dimerization) derived from ABA was developed and used to control gene activation, signal transduction, and cytoskeletal remodeling in response to Fe. This technology was utilized to design signal circuitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…To introduce the light control capacity in the ABA-CIP-based m 6 A editing platform, we incorporated the photo-caged ABA that allowed the activation of ABA, and therefore, inducing the RNA m 6 A editing, by light. We have shown that ABA can be caged with sensor units responsive to different stimuli and ABA can only be activated to induce CIP-controlled effects when exposed to the corresponding signals including light 46 48 . To create a light-inducible m 6 A editing system, we used 4,5-dimethoxy-2-nitrobenzyl (DMNB)-caged ABA, which can be uncaged by UV light 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To introduce the light control capacity in the ABA-CIP-based m 6 A editing platform, we incorporated the photo-caged ABA that allowed the activation of ABA, and therefore, inducing the RNA m 6 A editing, by light. We have shown that ABA can be caged with sensor units responsive to different stimuli and ABA can only be activated to induce CIP-controlled effects when exposed to the corresponding signals including light 46 48 . To create a light-inducible m 6 A editing system, we used 4,5-dimethoxy-2-nitrobenzyl (DMNB)-caged ABA, which can be uncaged by UV light 48 .…”
Section: Resultsmentioning
confidence: 99%
“…This strategy and platform will expand the existing toolbox for studying the dynamic biological function of RNA modifications in biological or disease processes. By caging ABA with other sensor units other than photo-caging groups 46 , 47 , these RNA epigenetic editing events can be coupled to various cellular signals, which can lead to new synthetic biology strategies in engineering mammalian cells for research or therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Several light-inducible methods based on CIP have been reported using CIP inducers caged with different photosensitive groups. These caged CIP inducers (including ABA, rapamycin, gibberellic acid, and other synthetic dimerizers) [77,[97][98][99][100][101][102][103][104][105][106][107][108] were inactive for dimerization in the caged form but can be uncaged to regenerate active inducer upon light irradiation. This photo-controlled version of CIP should be readily adaptable for light inducible epigenome editing.…”
Section: Light Inducible Epigenome Editingmentioning
confidence: 99%
“…This technology is based on the chemically induced proximity methods, utilizing artificially applied chemical inducers to control the proximity between two chosen cellular proteins and, in turn, control the downstream events resulting from protein association. 75,76…”
Section: Day 3—addressing Challenges In Diseases With Chemical Biologymentioning
confidence: 99%